Chitosan-zinc oxide nanoparticle composite coating for active food packaging applications. (December 2016) - Al-Naamani, Laila; Dobretsov, Sergey; Dutta, Joydeep
Abstract: In this study antimicrobial properties of chitosan and chitosan-zinc oxide (ZnO) nanocomposite coatings on PE films were studied. Oxygen plasma pretreatment of PE films led to increased adhesion by 2% of chitosan and the nanocomposite coating solutions to the packaging films. Scanning Electron Microscopy (SEM) revealed uniform coatings on PE surfaces. Incorporation of ZnO nanoparticles into the chitosan matrix resulted in 42% increase in solubility; swelling decreased by 80% while the water contact angle (WCA) increased from 60° to 95° compared to chitosan coating. PE coated with chitosan-ZnO nanocomposite films completely inactivated and prevented the growth of food pathogens, while chitosan-coated films showed only 10-fold decline in the viable cell counts of Salmonella enterica, Escherichia coli and Staphylococcus aureus after 24-h incubation compared to the control. Industrial relevance: One of the greatest challenges of food industry is microbial contamination. The present study suggests that PE coating with chitosan-ZnO nanocomposite is a promising technique to enhance antimicrobial properties of the films. Chitosan-ZnO nanocomposite coatings improved antibacterial properties of PE by inactivating about 99.9% of viable pathogenic bacteria. Hence, our results show the effectiveness of the nanocomposite coating in the development of active food packaging in order to prolong the shelf life of food products. Highlights: A chitosan-ZnO nanocomposite coating on polyethylene films was developed. Solubility of the chitosan-ZnO nanocomposite coating increased by 42% and swelling reduced by 80% compare to chitosan. Viability of E. coli, S. enterica and S. aureus cultures was reduced by 99.9% upon using the nanocomposite coating. Nanocomposite coatings are a promising method for active food packaging.